Adjuvant radiotherapy after local excision of rectal cancer. (1st April 2019) - Jones, H. J. S.; Cunningham, C.
Abstract: Background: Local excision is now accepted as a standard treatment option for certain patients with early rectal cancer. However, there is a higher risk of local recurrence than after radical surgery with total mesorectal excision. Adjuvant radiotherapy after local excision may reduce this excess risk, and yet retain the benefits of local excision, with rectal preservation. Methods: A review of the literature pertaining to the use of adjuvant radiotherapy after local excision of rectal cancer and a discussion of current practice. Results: We first considered local excision as a treatment option for early rectal cancer, looking at technical developments and the risks and benefits of organ preservation, in particular, the advantages for quality of life and the risk of leaving residual disease which may result in local recurrence. We then looked at reported outcomes for studies using adjuvant radiotherapy after local excision. Few of the studies routinely used modern endoscopic methods of local excision and only the recent used chemoradiation. Local recurrence rates after adjuvant radiotherapy have improved over time, with rates of around 3.5% in the recent studies. Adverse effects of adjuvant radiotherapy are not commonly described, but generally, they are relatively mild when described. We then discussed current practice regarding adjuvant radiotherapy, including pathological criteria, discussion of local recurrence risk with the patient and the importance of a surveillance regime to detect any recurrence at an early stage. Conclusion: We conclude that the current state of knowledge regarding adjuvant radiotherapy after local excision suggests a potential role in decreasing the risk of local recurrence but further studies are required to better define this effect, clarify which patients will gain the most benefit from this pathway, and identify those who should avoid exposure to the risks of radiotherapy.